2018
DOI: 10.1108/ijopm-04-2017-0204
|View full text |Cite
|
Sign up to set email alerts
|

The impact of servitization on firm performance: a meta-analysis

Abstract: Purpose Servitization has been recognized as an effective means for manufacturers to achieve superior performance. However, the servitization-performance relationship is controversial since prior empirical studies have provided inconsistent and even contradictory results. Hence, the purpose of this paper is to provide a quantitative review on the servitization-performance relationship based on research findings reported in the extant literature. Design/methodology/approach Studies from 41 peer-reviewed journ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
222
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(242 citation statements)
references
References 92 publications
19
222
1
Order By: Relevance
“…Prior studies compared the ambidexterity effects on varied measures such as firm performance, supply chain competence, supplier product innovation, cooperative innovation, helping firms to create advantageous environments ( Cao et al, 2009 ; Gualandris et al, 2018 ; Bravo et al, 2018 ; Wang et al, 2018 ; Crescenzi and Gagliardi, 2018 ). Ponis and Koronis (2012) examined the SC network proactive plan and design ability to predict unexpected disruptive events, and adaptively respond to, while preserving the SC structure and function, and exceeding to a post operations-robust stage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies compared the ambidexterity effects on varied measures such as firm performance, supply chain competence, supplier product innovation, cooperative innovation, helping firms to create advantageous environments ( Cao et al, 2009 ; Gualandris et al, 2018 ; Bravo et al, 2018 ; Wang et al, 2018 ; Crescenzi and Gagliardi, 2018 ). Ponis and Koronis (2012) examined the SC network proactive plan and design ability to predict unexpected disruptive events, and adaptively respond to, while preserving the SC structure and function, and exceeding to a post operations-robust stage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Servitization has received increasing attention from both practitioners and scholars and has evolved into a broader cross-disciplinary area in service research (Oliva and Kallenberg 2003; Wise and Baumgartner 2000). Originally conceptualized by Vandermerwe and Rada (1988), servitization refers to value creation by adding services to products and defined as a “transformational process of adding services to products with a strategic transition from goods-dominant logic to service-dominant logic” (Wang, Lai, and Shou 2018, p. 1564). Servitization has become a route to improving profits and maintaining firm stability (Spohrer and Maglio 2008; Wise and Baumgartner 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A decade ago, Neely (2008) reported that about a third of manufacturing firms were servitizing, and large firms such as IBM and Rolls Royce continue to derive a greater proportion of their revenues from services. Despite the growing prevalence of servitization, “the extant literature shows mixed findings” (Wang, Lai, and Shou 2018, p. 563), including the conclusion that more service infusion may not always be better (Forkmann et al 2017), and even that servitization can increase bankruptcy risk (Benedettini, Swink, and Neely 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Toyota uses 'Do not buy a forklift', Rolls-Royce applies 'Total Care Package' and 'Power by the Hour'. Also, Xerox implement documentation management business model rather than buying their machines (Wang et al, 2011;Elnadi and Shehab, 2016;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%